Effect of consumption of bee products on telomere lenght and longevity of life in beekeepers - Mohamad Nasir, Nurul Fatihah (2015)
The belief that beekeepers live longer than anyone else is present since ages and no research has been done to explore their longevity. Research has shown that telomere is associated with the longevity of life. Hence, this study aimed to investigate the telomere length in 30 male beekeepers and 30 male non-beekeepers and associate them with the longevity of life. Southern blot analysis of terminal restriction fragments (TRFs) was carried out by HinfI/RsaI digestion of human genomic DNA using TeloTAGGG Telomere Length Assay. Interestingly, the present study found that the telomere length of male beekeepers was significantly longer than those of male non-beekeepers with a p-value of less than 0.05, suggesting that beekeepers may have longer life compared to non-beekeepers. It was further found that the consumption of bee products for a long period and frequent consumption of bee products per day are associated with telomere length. A year increase in consuming bee products is associated with a mean increase in telomere length of 0.258 kbp. In addition, an increase in frequency of consuming bee products per day was also associated with a mean increase of 2.66 kbp in telomere length. These results suggest that bee products might play a role in telomere length maintenance.